Selfie pictures and the rituals of celebrating the Prophet’s mohamed birthday in the Othmanin Zaouia of tolga. From a technology to becoming a- Selfie tool- anthropological research. - نوار خرخاشي عبد المنعم; معتوق جمال (International Journal of Social Communication, 2024)
This article embodies the result of field work in tracking the rituals of celebrating the Prophet’s Mohamed birthday in the Othmanin Zaouia of tolga-Biskra. used phone technology for Selfie photo, than to becoming the Selfie tool in collecting data pictures and of various ceremonial practices and rituals photos.this procedure to embody the presence of the researcher within the community of his research on the one hand, and to establish those rituals, their embodiments and the places in which he was present on the other hand, the Selfie tool in research - which we introduced to the field of anthropology according to the terms of use set by the researcher as scientific standpoint.In a systematic way, because of the quality of the images captured in reviving those rituals.whenever the data of the -Selfie tool- images is examined with high quality, it enables him to experience,According to the Selfie tool, it is a qualitative addition to social research and anthropology